Impact of Organic Nutrient Management Practices on Growth and Yield of Mungbean - Joshi, N.; Joshi, S.; Singh, S.; Sharma, J. K.; Shekhawat, H. S.; Sutaliya, R. (International Journal of Bio-resource and Stress Management, 2022)
A multilocation field experiment was conducted during kharif season (July–September) of 2019 in mungbean under organic nutrient management at Agriculture Research Sub-Station, Sumerpur, Pali and Adaptive Trial Centre, Sumerpur, Pali, Rajasthan, India. The nine organic nutrient management practices viz. T1- Farmyard manure (FYM) as per soil health card @ 10 t ha-1, T2- Vermicompost @ 2 t ha-1, T3- T1+Vermiwash @ 10% at 15, 30 and 45 days after sowing (DAS), T4- T2+Vermiwash @ 10% at 15, 30 and 45 DAS, T5- T1+Panchgavya @ 4% at 15, 30 and 45 DAS, T6- T2+Panchgavya @ 4% at 15, 30 and 45 DAS, T7- T1+Panchgavya @ 6% at 15, 30 and 45 DAS, T8- T2+Panchgavya @ 6% at 15, 30 and 45 DAS and T9- Control in three replications in randomized complete block design (RCBD). The higher values of growth attributes like number of leaves, number of branches, height and leaf area per plant were recorded by treatment vermicompost as per soil health card+Panchgavya @ 4% at 15, 30 and 45 days after sowing (DAS) which was found significantly superior over the other treatments at both the places. It was found that Panchgavya @ 4% at 15, 30 and 45 DAS along with vermicompost @ 2 t ha-1 obtained higher SPAD value (39.51), seed yield (908 kg ha-1) and benefit cost ratio (B:C ratio) under organic farming during kharif season at both the places.